A Meta-Analysis on the Relationship Between Prayer and Student Outcomes. Issue 8 (November 2020) - Jeynes, William
A meta-analysis, including 13 studies, was undertaken on the relationship between the exercise of student prayer and academic and behavioral outcomes in urban schools. Analyses both with and without sophisticated controls (e.g., socioeconomic status, race, and gender) were used. Additional analyses were done to determine whether the effects of prayer differed by the quality of the study. The results indicated that the exercise of prayer is associated with better levels of student outcomes. Moreover, the effects of prayer were greater for high-quality studies. The significance of these results is discussed.